Large-Scale Cultivation of Spirulina for Biological CO2 Mitigation in Open Raceway Ponds Using Purified CO2 From a Coal Chemical Flue Gas - Zhu, Baohua; Shen, Han; Li, Yun; Liu, Qiuke; Jin, Guiyong; Han, Jichang; Zhao, Yan; Pan, Kehou (Frontiers in Bioengineering and Biotechnology, 2020)
In order to select excellent strains with high CO2 fixation capability on a large scale, nine Spirulina species were cultivated in columnar photobioreactors by the addition of 10% CO2. The two species selected (208 and 220) were optimized for pH value, total dissolved inorganic carbon (DIC), and phosphorus content with intermittent CO2 addition in 4 m2 indoor raceway ponds. On the basis of biomass accumulation and CO2 fixation rate in the present study, the optimum pH, DIC, and phosphate concentration were 9.5, 0.1 mol L-1 and 200 mg L-1 for both strains, respectively. Lastly, the two strains selected were semi-continuously cultivated successfully for CO2 mitigation in 605 m2 raceway ponds aerated with food-grade CO2 purified from a coal chemical flue gas on a large scale. The daily average biomass dry weight of the two stains reached up to 18.7 and 13.2 g m-2 d-1, respectively, suggesting the two Spirulina can be utilized for mass production.